Reading John in Ephesus - Tilborg, Sjef van (Novum Testamentum / Supplements, 1996)
This study describes the embedding of the Gospel of John in the city life of Ephesus. It uses the epigraphical and historical materials of first-century Ephesus as the point of reference for a reading of John. The study is a specific demonstration of the linguistic supposition that the use of the same (combination of) words in different co-texts evokes semantic similarities and dissimilarities which influence the process of giving meaning to a text. Reading John against the background of Ephesus influences its impact. Five topics have been selected: the use of names; the use of the titles for the emperors and Artemis in relation to the titles used for Jesus; the social city life; the group formations; and the function of the high priests in relation to the imperial cult.